Biosynthesized unmodified silver nanoparticles: A colorimetric optical sensor for detection of Hg2+ ions in aqueous solution - Harisha K. Sanjeevappa; Parushuram Nilogal; Ranjana Rayaraddy; Lavita J. Martis; Samir M. Osman; Narayana Badiadka; Sangappa Yallappa (Results in Chemistry, 2022)
Under the catalysis of microwave radiation, silver nanoparticles (AgNPs) were synthesized in situ by reducing silver ions (AgNO3) using the phenolic hydroxyl groups of the tyrosine domain in silk sericin. The dispersion synthesized nano-biocomposite was characterized using different analytical instruments. The surface Plasmon resonance (SPR) absorption band observed at 412 nm in UV–visible (UV–vis) spectra confirm the generation of AgNPs. The FCC crystal structure and generation of Ag0 atoms were revealed by powder X-ray diffraction analysis and X-ray photoelectron spectroscopy respectively. Transmission electron microscopy (TEM) was used to investigate the distribution, shape evolution, size of AgNPs, and the finding revealed a spherical morphology with an average size of 8.4 nm. The sericin synthesized AgNPs were used to detect mercury ions (Hg2+) in an aqueous solution selectively and sensitively, and the interaction response was monitored using UV–vis spectroscopy. As Hg2+ was added to AgNPs, the overall absorbance dropped significantly, and the color changed from yellow to colorless. With the best linearity fit (R2 = 0.995) in the concentration range of 10–100 ppb, the maximum of detection (LOD) was about 15 ppb. Bio-based AgNPs can prove to be an excellent material for optical sensors.